A study of spot urine protein: creatinine ratio as an alternative to 24 hours proteinuria for the diagnosis of pre-eclampsia - Sarkar, Ruma; Rawat, Shilpi; Sharma, Neela Rai; Tiwari, Harish Chandra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Preeclampsia is defined as systolic blood pressure level of 140 mmHg or higher or a diastolic blood pressure level of 90 mmHg or higher that occurs after 20 weeks of gestation with proteinuria. Objective of this study was to study the role of spot urine protein: creatinine ratio as an alternative to 24 hours proteinuria for the diagnosis of pre-eclampsia Methods: This is a prospective observational study conducted in the department of obstetrics and gynaecology, BRD Medical College Gorakhpur, since October 2016 to September 2017 included 120 pregnant women with hypertension of gestational age more than 20 weeks. Ramdom urine sample of all the patient was taken before 12 noon after first voiding. For 24 hours urine sample patient was asked to collect all her urine she voids during 24 hours. The creatinine was estimated by the alkaline picrate method (Jaffe's Reaction) modified by the Bonsnes and Taussky, 1945. Creatinine in a protein free solution reacts with the alkaline picrate and produces red colour complex which is measured colorimeterically. Urinary protein was estimated in all the subjects by the Turbidimetric method. Urinary protein was precipitated by 3% sulphosalicylic acid and turbidity so produced was measured colorimetrically. Results: Protein: creatinine ratio in a random urine sample is better than random urine protein detection by dipstick method in cases of emergency when there is no time for detection of 24 hours urine protein. Conclusions: If cut-off level for urine protein: creatinine ratio in random urine sample is taken as 0.25 or more then sensitivity and specificity become same as 24 hours urine protein.